Pengaruh Platform Merdeka Mengajar dan Evaluasi Kinerja terhadap Kompetensi Guru SMP di Kecamatan Mesuji - Duwi Agustina; Edi Harapan; Nila Kesumawati (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study aims to analyze the influence of the Merdeka Mengajar Platform and performance evaluation on the competence of junior high school teachers in Mesuji District. Teacher competence plays a crucial role in improving the quality of education; therefore, the use of learning technology and effective evaluation systems is essential. The Merdeka Mengajar Platform, as an innovation initiated by the Ministry of Education, provides various learning resources, teaching tools, and training that help teachers enhance their professionalism. Meanwhile, performance evaluation serves as a benchmark to assess how well teachers carry out their duties according to established standards. This research employs a quantitative approach with a survey method, where data were collected through questionnaires distributed to junior high school teachers in Mesuji District. Data were analyzed using multiple regression techniques to determine the contribution of each variable. The results reveal that the use of the Merdeka Mengajar Platform significantly affects the improvement of teacher competence, particularly in pedagogical and professional aspects. In addition, performance evaluation also shows a positive effect in encouraging teachers to be more disciplined, innovative, and responsible in their work. Simultaneously, both variables contribute significantly to enhancing teacher competence. These findings imply that optimizing the use of the Merdeka Mengajar Platform, supported by measurable performance evaluation, can be an effective strategy to improve the quality of education at the junior high school level.